Land flatworms of the genus Pasipha (Platyhelminthes, Geoplanidae) in Argentina, with description of three new species - Negrete, Lisandro; Brusa, Francisco (Zootaxa, 2016)
The genus Pasipha Ogren & Kawakatsu, 1990 currently includes 22 species, most of them recorded in the Brazilian Atlantic Forest. Recently, Pasipha hauseri was documented in north-eastern Argentina, thus extending its distribution range. This paper reports new records of the genus Pasipha in the Interior Atlantic Forest ecoregion in Argentina, with the description of three new species: Pasipha atla sp. nov., Pasipha johnsoni sp. nov., and Pasipha mbya sp. nov. These new species exhibit similarities in internal anatomy, such as pharynx cylindrical, extrabulbar prostatic vesicle with folded walls and proximally forked, male atrium highly folded, being at least two times longer than the female atrium and with small folds in their proximal portion. However, they can be distinguished from each other mainly by the secretion types discharged into the prostatic vesicle as well as into the male and female atria. In addition, they have different colour patterns on the dorsal surface.